Optimized Dual-Band Reconfigurable Power Amplifier for 5G - Mouad, El Kobbi; Bendali, Abdelhak; Zarrik, Samia; Habibi, Sanae; El Wardi, Reda Abid; Habibi, Mohamed (IAES Indonesian Section, 2025)
This article presents the design of a dual-band power amplifier capable of operating in three different classes: A, AB, and B. Simulation results reveal that a single power amplifier can efficiently operate at two specific frequencies of the 5G core band, namely 3.5 GHz and 3.8 GHz. The amplifier demonstrates exceptional stability and matching across both frequency bands. It achieves a maximum gain of 17.7 dB, a maximum output power of 41.2 dBm, and a maximum power-added efficiency (PAE) of 70%. These performance characteristics are achieved through an innovative design that allows for frequency band reconfiguration via a PIN diode switch, as well as the selection of the operating mode among classes A, AB, and B. This flexibility makes the amplifier ideal for applications in 5G communication systems, offering an optimal balance between linearity, energy efficiency, and overall performance